2016
DOI: 10.1007/s10495-016-1291-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing effect of juglone is mediated by down regulation of Notch1 signaling pathway in trastuzumab-resistant SKBR3 cells

Abstract: Trastuzumab (Herceptin) monoclonal antibody directed against HER2 receptor has been administered as a treatment for metastatic HER2 positive breast cancer. The problematic issue in treatment of HER2 positive breast cancer cells is commonly the induction of resistance to trastuzumab which might be due to modulation of some vital signaling elements such as Notch1 and Pin1. In this study, we were aimed to investigate whether the cross talk between pin1 and Notch1 has a role in this event. Our results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Recently, a novel Pin1 inhibitor, KPT-6566, inhibits the PPIase activity and induces the degradation of Pin1 by covalently interacting with its catalytic core 38 . Moreover, inhibiting Pin1 sensitizes many cancer cells to chemotherapy, including HCC to sorafenib 228 , breast cancer to trastuzumab 229 , rapamycin 53 , Taxol and 5-fluorouracil 141 , colon cancer to Taxol 84 , and AML to retinoic acid 81 . Increasing evidence showed that Pin1 is a potential target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel Pin1 inhibitor, KPT-6566, inhibits the PPIase activity and induces the degradation of Pin1 by covalently interacting with its catalytic core 38 . Moreover, inhibiting Pin1 sensitizes many cancer cells to chemotherapy, including HCC to sorafenib 228 , breast cancer to trastuzumab 229 , rapamycin 53 , Taxol and 5-fluorouracil 141 , colon cancer to Taxol 84 , and AML to retinoic acid 81 . Increasing evidence showed that Pin1 is a potential target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Interestingly, Pin1 overexpression has also recently been linked to trastuzumab resistance, and inhibition of Pin1 may help sensitize resistant cells to treatment. 52 Further exploration of the relationship between Pin1, CDKs, and the Smad3/TGFb pathway in HER2C as well as triple negative disease may provide important insights into key mechanisms of treatment resistance for these aggressive breast cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch pathway is a highly conserved cell signaling pathway that plays a pivotal role in a variety of cellular processes, including proliferation, invasiveness and drug resistance [22,23]. Moreover, Notch1 is critical in cell fate decisions in the developing nervous system and several cancer cells, whist its activation is also involved in chemoresistance processing [24,25].…”
Section: Ivyspringmentioning
confidence: 99%